Rancang Bangun Sistem Reservasi Kamar pada Manadia Guest House Manado berbasis Web - Fergie Joanda Kaunang (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2020)
The development of the technological world is currently experiencing increasingly rapid development. Information technology is no longer just a field of science but also an integral part of the world of business, industry, education and social relations. The hotel or lodging business is one of the growing businesses because it operates 24 hours a day throughout the year without exception regarding holidays. This can be one of the opportunities for the industrial world including the hotel industry to take advantage of advances in information technology by developing computerized systems that can be a means to facilitate those that hotel or lodging services. With the development of a computerized system, processes such as booking a room, providing information to consumers can be done easily. This research aims to design a room reservation system in one of the inns in the city of Manado, Manadia Guest House. The analysis and design of the system in this study uses the UML (Unified Modeling Language) approach, while the system development uses the Prototyping method. The results of this study are a computerized system designs which can be used to facilitate and improve the business processes that exist at Manadia Guest House.